Asphyxial games or "the choking game": a potentially fatal risk behaviour. Issue 1 (3rd February 2009) - Macnab, A J; Deevska, M; Gagnon, F; Cannon, W G; Andrew, T
Abstract : Objectives: To determine the prevalence of knowledge about and participation in asphyxial games, sometimes called "the choking game", and how best to raise awareness of this risk-taking behaviour and provide preventive education. Design: Questionnaire; collaborative research model; lay advocacy group/university researchers. Setting: 8 middle and high schools in Texas (six) and Ontario (two). A recent death from playing the choking game had occurred in one Texas school, and two other fatalities had occurred within the state. Subjects: Students in grades 4–12, aged 9–18 years. Intervention: None. Outcome measures: None. Results: Of 2762 surveys distributed, 2504 (90.7%) were completed. The mean (SD) age of the responders was 13.7 (2.2) years. 68% of children had heard about the game, 45% knew somebody who played it, and 6.6% had tried it, 93.9% of those with someone else. Forty percent of children perceived no risk. Information that playing the game could result in death or brain damage was reported as most likely to influence behaviour. The most respected source of a preventive education message was parents for pre-adolescents (43%) or victim/victim's family (36%) for older adolescents. Conclusions: Knowledge of and participation in self-asphyxial behaviour is not unusual among schoolchildren. The age of the child probably determines the best source (parents or victim/victim's family) of preventive education.